Effect Of Diaphragmatic Breathing Exercise In Padmasana And Vajrasana Position And Jacobson Relaxation Technique In Young Adults With Pre- Hypertension And Anxiety On Cardio-Respiratory System And Psychology (International Journal of Environmental Sciences, 2025)
Introduction:Prehypertension is commonly observed in young adults with anxiety, often leading to increased blood pressure and respiratory rate.Objective:To evaluate the effectiveness of Vajrasana and Padmasana positions combined with diaphragmatic breathing and Jacobson relaxation in young adults with anxiety and prehypertension.Method:Sixty participants were divided into two groups (30 each). Group A practiced Vajrasana, and Group B practiced Padmasana, both with DBE and JRT for 15 minutes, 4 days a week over 8 weeks. BP, RR, and anxiety levels were recorded pre- and post-intervention.Results:Both groups showed significant improvement in RR (p=0.732) and anxiety (p=0.509), but Group A showed greater improvement in systolic (p=0.000) and diastolic BP (p=0.006).Conclusion:While both positions improved RR and anxiety, Vajrasana with DBE and JRT was more effective in reducing blood pressure, showing greater overall benefits.